New Subtype B Containing HIV-1 Circulating Recombinant of sub-Saharan Africa Origin in Nigerian Men Who Have Sex With Men. (15th August 2019) - Billings, Erik; Kijak, Gustavo H.; Sanders-Buell, Eric; Ndembi, Nicaise; O'Sullivan, Anne Marie; Adebajo, Sylvia; Kokogho, Afoke; Milazzo, Mark; Lombardi, Kara; Baral, Stefan; Nowak, Rebecca; Ramadhani, Habib; et al.
Abstract : Background: HIV-1 circulating recombinant forms (CRF) containing subtype B are uncommon in sub-Saharan Africa. Prevalent infections observed during enrollment of a prospective study of men who have sex with men (MSM) from Lagos, Nigeria, revealed the presence of a family of subtype B and CRF02_AG recombinants. This report describes the HIV-1 genetic diversity within a high-risk, high-prevalence, and previously undersampled cohort of Nigerian MSM. Methods: Between 2013 and 2016, 672 MSM were enrolled at the Lagos site of the TRUST/RV368 study. Prevalent HIV-1 infections were initially characterized by pol sequencing and phylogenetic subtyping analysis. Samples demonstrating the presence of subtype B were further characterized by near full-length sequencing, phylogenetic, and Bayesian analyses. Results: Within this cohort, HIV-1 prevalence was 59%. The major subtype was CRF02_AG (57%), followed by CRF02/B recombinants (15%), subtype G (13%), and smaller amounts of A1, B, and other recombinants. Nine clusters of closely related pol sequences indicate ongoing transmission events within this cohort. Among the CRF02_AG/B, a new CRF was identified and termed CRF95_02B. Shared risk factors and Bayesian phylogenetic inference of the new CRF95_02B and the similarly structured CRF56_cpx indicate a Nigerian or West African origin of CRF56_cpx before its observation in France. Conclusion: With high HIV-1 prevalence, new strains, and multiple transmission networks, this cohort of Nigerian MSM represents a previously hidden reservoir of HIV-1 strains, including the newly identified CRF95_02B and closely related CRF56_cpx. These strains will need to be considered during vaccine selection and development to optimize the design of a globally effective HIV-1 vaccine. Abstract : Supplemental Digital Content is Available in the Text.